Effective Interventions for Improving Functional Movement Screen Scores Among “High-Risk” Athletes: A Systematic Review - Sean C. Clark; Nicholas D. Rowe; Mohamed Adnan; Symone M. Brown; Mary K. Mulcahey (International Journal of Sports Physical Therapy)
# Background